IMPLEMENTASI ISO 90012015 DI FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Yuni Nurjanah (Jurnal Pustaka Ilmiah, 2016)
This paper discusses the implementation of ISO 9001: 2015 at the Faculty of EngineeringDiponegoro University. The purpose of writing this paper is to determine the stagesor implementation process, advantages and disadvantages. Based on the results of thediscussion in this paper, it is concluded that the implementation process of ISO 9001:2015 to obtain certification requires 5 (five) phases, namely (1) assessment of currentsystem, (2) design, development and review, (3) implementation,) Audit and review,and (5) certification readiness. Benefits of the implementation of ISO 9001: 2015 inthe Faculty of Engineering Diponegoro University, including: to ensure customersatisfaction of products or services sold, increase customer confidence, instill a senseof pride for employees so motivate them to work and work better, facilitate Faculty ofEngineering Diponegoro University To gain cooperation from more business partners,as a material to analyze institutional capabilities, improve risk control managementso that institutions are more stable, organizational systems become more organizedand directed. The obstacles encountered in this ISO implementation include: funding,commitment of all relevant parties, and consistency in running ISO 9001: 2015.